EFFCT OF AUTUMN AND WINTER SEASONS ON SEMINAL TRAITS AND TESTICULAR MEASUREMENTS OF AWASSI RAM LAMBS - Khalil, Raaed I. (Diyala Agricultural Sciences Journal, 2018)
The objective of this study was to compare between the effect of autumn (decrease daylight) and winter (increase daylight) seasons on some reproductive traits in Awassi ram lambs for selecting them on the onset of sexual activity as in their flock . This study was performed at the Ruminant Research Station, Abu Ghraib- belong to the Directorate of Agricultural Researches during the two periods, autumn (17-24 November ) and winter (26 January –3 February) seasons using twelve Awassi ram lambs aged 12-13 month. The study has observed non-significant difference between seasons for semen parameters, seminal plasma parameters, testosterone, cortisol concentrations, testicular measurements and reaction time. However, this study revealed positive correlation between ejaculate volume and total spermatozoa per ejaculate(P≤0.01), mass activity and individual motility (P≤0.01), semen protein with seminal triglyceride (P≤0.01), seminal protein and seminal cholesterol (P≤0.05) and seminal cholesterol with seminal Aspartate Aminotransferase (AST) (P≤0.05).In conclusion, the costs were reduced depending on autumn season for estimation the sexual activity of ram lambs to select them for the sheep flocks.